Exploring the Effectiveness of Personal Vocabulary Note in Enhancing English Vocabulary Mastery at SMPN 1 Baranti - Nur Sadriana Syahrir; Syamsu T; Nurul Faradillah; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to Exploring the effectiveness of the Personal Vocabulary Note (PVN) technique in enhancing the English vocabulary mastery of seventhgrade students at SMPN 1 Baranti. A quantitative method with a quasi-experimental design was employed, involving two groups: an experimental group taught using the PVN technique and a control group taught using conventional methods. The research instrument was a multiple-choice vocabulary test administered before (pre-test) and after (post-test) the treatment. The results showed an increase in the average score from 54.69 in the pretest to 81.88 in the post-test. Data analysis using the Independent Samples t-Test revealed a significance value of less than 0.001, indicating a statistically significant difference between the two groups. Thus, the PVN technique proved effective in improving students' vocabulary mastery. Additionally, it encouraged students to study independently and actively develop their English language skills. Therefore, the PVN technique can be considered an alternative teaching strategy recommended for vocabulary instruction at the junior high school level.